INTERACTION STUDIES OF AMINO ACIDS IN AQUEOUS SODIUM BROMIDE SOLUTIONS AT DIFFERENT TEMPERATURE - Akhtar, Yasmin (International Journal of Research -GRANTHAALAYAH, 2017)
Densities, ultrasonic velocities and viscosities of L- Valine and L- Phenylalanine in aqueous sodium bromide (0.00, 0.025 and 0.05) m solutions have been determined experimentally at 308 and 313 K. The results obtained from density ultrasonic velocity and viscosity measurement have been used to calculate the apparent molal volume, фv, apparent molal, adiabatic compressibility ф Ks, partial molal volume ф0v at infinite dilution, partial molal adiabatic compressibility ф0Ks at infinite dilution, transfer volume ∆ф(tr), experimental slopes Sv and SKs,Falkenhagen coefficient A and Jones-Dole B coefficient. The results are discussed in terms of the dehydration effect of the sodium bromide upon the amino acids and weak solute- solute and strong solute- solvent interactions. The properties of these amino acids in water and water + sodium bromide solution systems are discussed in terms of the charge, size and hydrogen bonding effect.